The unlocked leader dare to free your own voice, lead with empathy, and shine your light in the world - Gentil, Hortense le; Lambert, Caroline (Ascent Audio, 2023)
"The most effective leaders are ""human leaders:"" leading with empathy, vulnerability, and authenticity. But many still adhere to the outdated myth that leaders must be ""superhero leaders: infallible, unflappable, and fearless."" Tragically, their innate ability to inspire remains locked within, blunting their impact. In The Unlocked Leader veteran executive leadership coach Hortense le Gentil combines real life stories, rigorous research, and practical tools to explain how superhero leaders can become effective human leaders. You'll discover: - How to identify the mental obstacles that stand between you and leadership authenticity, and sap your energy and impact-your mindtraps. - How to confront your fears and escape those traps by operating a mindshift. - Practical strategies to better connect with yourself and others-a mindbuild. An indispensable leadership manual for people who wish to lead not just with their heads, but with their heart and soul as well, The Unlocked Leader belongs on the bookshelves of leaders and aspiring leaders at all levels looking for a fresh new perspective on effective, powerful leadership in service of something bigger than themselves."